Status of N P K in Vermicompost Prepared from Two Common Weed and Two Medicinal Plants - Mistry, Jayanta; Mukhopadhyay, Ambika Prasad; Baur, Gopi Nath (International Journal of Applied Sciences and Biotechnology, 2015)
Vermicomposting is a bio-technique and vermicompost are good superlatives for organic farming. During vermicomposting the nutrients are released and converted into soluble and available forms that’s providing nutrients such as available N (nitrogen), soluble K (potassium), exchangeable Ca (calcium), Mg (magnesium), P (phosphorus) and microelements such as Fe (iron), Mo (molybdenum), Zn (zinc), and Cu (cupper) which can easily taken up by plants. Vermicompost contains plant growth regulators, soil treated with vermicompost showed better plant growth than treated with inorganic and other organic fertilizers. Adding of vermicompost to soil improves the soil structure, increasing the water holding capacity and porosity. Vermicomposts have also been shown to suppress attacks by soil and foliar transmitted plant diseases.This article reviews various attribute as NPK values of Parthenium hysterophorus, Azadirachta indica, Argemone mexicana, and Vitex negundo vermicompost. pH of each compost are in range of 7.5 – 8.1. Nitrogen (N) content (%) is low in cow dung compost (1.7%) and higher in other plant compost except Azadirachta indica and Vitex negundo, maximum in Parthenium vermicompost (1.8%). Phosphorus (P %) ranges 1.3% to 1.6% and maximum in Azadirachta indica vermicompost. Potassium (K %) ranges 0.8% to 15.8% and all four vermicompost has significantly higher K contents than the cow dung compost. Organic carbon - nitrogen ratios (C/N) were also higher in vermicomposts produced with plant except in Argemone mexicana. Int J Appl Sci Biotechnol, Vol 3(2): 193-196 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12533